Convergence of a formal power series and Gelfond-Leont’ev derivatives - S. I. Fedynyak; M. M. Sheremeta (Математичні Студії, 2011)
Given a formal power series, we establish conditions on the formal power seriess under which the series represents a function analytic in the disk {z:|z|≤R},R∈(0,+∞]. We also give a survey of well-know results for the case R=+∞.